Skinhead culture: the ideologies, mythologies, religions and conspiracy theories of racist skinheads. (19th October 2016) - Pollard, John
ABSTRACT: Groups of racist skinheads now constitute a significant element of the global radical right. The British youth subculture of the late 1960s has thus been transformed into a worldwide social movement, the violent cutting-edge of white supremacist resistance to multiculturalism. Pollard examines the historical development of the racist skinhead phenomenon and, in particular, analyses the origins, nature and development of the ideas that inspire it: the foundational myth; 'skinhead, a way of life'; Odinism or paganism; the skinhead as victim ; skinheads as a vanguard of white, male, working-class revolutionaries; National Socialism and antisemitism; and, above all, racialism.